The role of the immunoproteasome in cardiovascular disease - Yifei Nie; Zhao Ma; Baoen Zhang; Meichen Sun; Dongfeng Zhang; Hui-Hua Li; Xiantao Song (Elsevier, 2024)
The ubiquitinproteasome system (UPS) is the main mechanism responsible for the intracellular degradation of misfolded or damaged proteins. Under inflammatory conditions, the immunoproteasome, an isoform of the proteasome, can be induced, enhancing the antigen-presenting function of the UPS. Furthermore, the immunoproteasome also serves nonimmune functions, such as maintaining protein homeostasis and regulating signalling pathways, and is involved in the pathophysiological processes of various cardiovascular diseases (CVDs). This review aims to provide a comprehensive summary of the current research on the involvement of the immunoproteasome in cardiovascular diseases, with the ultimate goal of identifying novel strategies for the treatment of these conditions.